Consortial effect of bio-inoculants for the management of powdery mildew of bhendi incited by Golovinomyces cichoracearum (DC.) V.P. Heluta - Sundaramoorthy, S; Lokesh, R; Jaiganesh, V; Kannan, C; Sivasakthivelan, P (Plant Science Today, 2025)
Powdery mildew of bhendi, incited by Golovinomyces cichoracearum (DC.) V.P. Heluta, results in substantial yield losses. To address this, an eco-friendly disease management strategy was developed using Ampelomyces quisqualis, Trichoderma harzianum and plant growth-promoting rhizobacteria (Bacillus subtilis). Strains AUAQ05 (A. quisqualis), AUTH02 (T. harzianum) and AUBS01 (B. subtilis) were evaluated for their efficacy against the pathogen under in vitro, pot culture and field conditions. In the in vitro spore germination assay, individual applications of AUAQ05 (84.64 %), AUTH02 (67.85 %) and AUBS01 (61.53 %) at 0.5 % concentration significantly inhibited conidial germination. Prior to combined application, the compatibility among the strains was assessed and confirmed. Under greenhouse (77.26 %) and field (71.69 %) conditions, the consortium of AUAQ05, AUTH02 and AUBS01 markedly reduced disease incidence. Additionally, field trials showed a 64.74 % increase in yield over the untreated control, surpassing the effect of individual treatments. These findings demonstrate that a compatible biocontrol consortium can serve as an effective and eco-friendly strategy for managing powdery mildew in bhendi.